Disaster songs as intangible memorials in Atlantic Canada - Sparling, Heather, 1972- (New York, NY : Routledge, 2023)
"Disaster Songs as Intangible Memorials in Atlantic Canada draws on a collection of over 500 Atlantic Canadian songs relating to disasters from 1891 up until the present, and describes the characteristics that define them as intangible memorials. The book demonstrates the relationship between vernacular memorials - informal memorials collectively and spontaneously created from objects and notes by the general public - and disaster songs. Author identifies the features that define vernacular memorials, and applies them to disaster songs: spontaneity; ephemerality; importance of place; motivations and meaning-making; content, as well as the role of media in inspiring and disseminating memorials and songs"--
Preface. Come All Ye -- Introduction -- Formal Memorials, Vernacular Memorials, and Disaster Songs -- Going Down in History : The Story of Disaster Songs -- Locating Meaning : The Place of Disasters in Songs -- Spontaneity & Ephemerality : The Timing of Memorialization -- Social Significance : The Motivation to Create Disaster Songs -- Personal Motivations : Relationships & Grief -- News & Social Media : Inspiring, Informing, and Disseminating Disaster Songs -- Conclusion.
Keywords: Disasters -- Atlantic Provinces -- Songs and music -- History and criticism; Memorialization -- Atlantic Provinces -- History; MUSIC / Ethnomusicology